Carbide-based thermal spray coatings: A review on performance characteristics and post-treatment. (February 2022) - Govande, Akshay R.; Chandak, Aayush; Sunil, B. Ratna; Dumpala, Ravikumar
Abstract: Components working under harsh environments in power generation, marine, and aerospace sectors are subjected to severe surface degradation because of wear, corrosion, and erosion by solid particles, slurry, silt, and cavitation. Carbide-based materials exhibit high resistance to degradation under such conditions because of their high hardness and chemical stability. These carbides can be effectively deposited as coatings on the components using advanced thermal spray techniques such as plasma spraying, HVOF, and HVAF. The carbide-based thermal spray coatings are majorly based on either WC or Cr3C2 or a combination of these materials. However, the composition of the carbides, the type and percentage of binders, and process parameters significantly affect the performance of these coated components. In this article, the degradation behavior and performance of the different carbide-based coatings as a function of carbide grain size and type of metallic binders, spray process parameters, and working conditions have been critically reviewed. On the other hand, the post-processing of carbide coatings is also emerging as a promising strategy to enhance the performance by modifying and refining the structure of coatings. Hence, a comprehensive summary of the post-processing techniques such as heat treatment, laser treatment, and cryogenic treatment of the carbide coatings is also provided. Highlights: Overview of the carbide coatings deposited by HVOF/HVAF/Plasma spray techniques WC and Cr3 C2 are widely used coating materials across the application domains. Wear and erosion performance of the carbide-based coatings are critically reviewed. The synergetic effect of cavitation and corrosion of carbide coatings are reviewed. Post-treatment and its effect on the performance of the carbide coatings are reviewed.